The impact of carbon emissions tax on vertical centralized supply chain channel structure. (March 2020) - Yu, Wei; Shang, Haitao; Han, Ruizhu
Highlights: Supply chain channel structure under carbon emissions tax is studied. More decentralized supply chain channel structure results in lower carbon tax level. Decentralization benefits a monopolistic manufacturer when its product emissions pollution is high enough. Decentralization benefits competing manufacturers when their product is more emissions polluting. Abstract: This paper studies the supply chain channel structure which is considered choosing either centralization or decentralization in both a single chain system with a single product and a two chains system with competition in the two substitutable products under carbon emissions tax, respectively. In the two cases, each chain consists of a retailer, who acts as a follower and a manufacturer who acts as a leader. Our analytical results show that: (i) When decentralization is practicable, the government is willing to set a lower carbon tax. (ii) In a single-chain system, the monopolistic manufacturer is better off under decentralization than under centralization when its product emissions pollution is high enough. (iii) In the two chains system, two manufacturers can benefit from decentralization when their product is more emissions polluting. Under certain conditions, comparing with centralization, decentralization enhances two manufacturers' profits through carbon emissions tax reduction and keeps consumer surplus and social welfare at the first-best level. (iv) The manufacturer's product quantity under decentralization is lower than that under centralization due to double marginalization effect, which also results in the lower environmental pollution. Our study also suggests that for the seriously emissions polluter, when it utilizes decentralization, the government have to introduce a lower carbon emissions tax in the consideration of abating environmental pollution and of maximizing its profits. The result can also benefit policy-makers in instructing firms to choose decentralization for promoting social development and environmental protection.